Spiritual well‐being and its relationship with patient characteristics and other patient‐reported outcomes in peritoneal dialysis patients: Findings from the PDOPPS. Issue 7 (10th March 2022) - Cheawchanwattana, Areewan; Kanjanabuch, Talerngsak; Puapatanakul, Pongpratch; Narenpitak, Surapong; Halue, Guttiga; Tungsanga, Kriang; Tatiyanupanwong, Sajja; Lorvinitnun, Pichet; Sritippayawan, Suchai; Chieochanthanakij, Rutchanee; Tungsanga, Somkanya; Thamcharoen, Natanong; et al.
Abstract: Background: Spiritual well‐being (SWB), an individual's understanding of the meaning and purpose of life, may help patients with chronic or terminal illnesses cope with their diseases. This study aimed to assess SWB in patients on peritoneal dialysis (PD), as well as its relationship with patient characteristics and patient‐reported outcomes (PRO). Methods: The data were obtained from questionnaires that formed part of the PD Outcomes and Practice Patterns Study (PDOPPS). Measures used in this study were SWB scores derived from the WHO quality of life, spirituality, religiousness and personal beliefs (WHOQOL‐SRPB) tool including 32 items from eight facets; physical (PCS) and mental component summary (MCS) scores of the 12‐Item Short‐Form Health Survey (SF‐12), Center of Epidemiologic Studies Depression Scale‐10 (CES‐D‐10) scores, burden of kidney disease scores and functional status scores. Results: Overall, 529 out of 848 participants (62%) completely responded to the questionnaires and were included in the analysis. Over two‐thirds of PD patients (70%) had moderate or higher SWB scores. The SWB scores were significantly lower in patients with age >65 years and unemployed status. SWB scores positively correlated with higher PCS, MCS, burden of kidney disease scores and functional status scores, while negatively correlated with depression scores by CES‐D‐10 scale. Patients who reported significant depressive symptoms (CES‐D‐10 score ≥ 10) had significantly lower SWB scores. Conclusion: Better SWB was significantly associated with better health‐related QOL (HRQOL) and the absence of depressive symptoms. SWB may be an essential consideration in the delivery of high‐quality PD. SUMMARY AT A GLANCE: This study examined spiritual well‐being (SWB, the understanding of the meaning and purpose of life by the patient), which is an unexplored area in the care of PD patients. It showed that SWB has a close relation with quality of life. The result suggests that SWB may be a target for intervention and patient education.